واقع نشاط العلاقات العامة في المنظمات السياحية : دراسة تطبيقية على عينة من الفنادق الممتازة - سعد ابراهيم علي (PROSPECTIVE RESEARCHES, 2023)
Organizations in general, and specially tourist organizations seek to achieve certain goals .to reach these goals they use all the available means and resources such as human and physical resources in order to servive and develop in the market. One of these means might be the activity of the general relations which assume the matual cooperation between the tourist organization and its clients. Administrative jobs in tourist organization are prone to be weak in the field of general relations, but, in fact, the emphasis on such jobs will lead to attract more clients, so we use some statistical methods such as percent ratio, means, correlation coeffient, and kay square law. We conclude that there is a shortage in the number of staff as wall as to confine their activities to secondary field, so we recommed to encourage operation and serivces departments to cooperate with general relations department.